Immunisation coverage and its determinants among Rohingya refugee children in Malaysia - Al-Haroni, Hanan; Muthanna, AbdulRahman; Mohd Desa, Mohd Nasir; Azzani, Meram (Royal Australian College of General Practitioners, 2023)
Background and objectives: The displacement of populations due to humanitarian emergencies has an adverse impact on the global elimination of vaccine-preventable diseases. However, the level of immunisation coverage among Rohingya refugee children remains unknown. Therefore, this study investigated immunisation coverage and its determinants among Rohingya refugee children in Malaysia. Methods: A cross-sectional study was conducted from September to November 2020 among the guardians of 243 Rohingya refugee children studying under the sponsorship of the King Salman Humanitarian Aid and Relief Center, Malaysia. Results: Among the 243 children, 90 (37) were unimmunised, 147 (60.5) were partially immunised and only 6 (2.5) were fully immunised. The country of childs birth, the childs age and access to healthcare services were significantly associated with unimmunisation (all P<0.05).